Responder Analyses from a Phase 2b Dose-Ranging Study of Bremelanotide. Issue 8 (2nd July 2019) - Althof, Stanley; Derogatis, Leonard R.; Greenberg, Sally; Clayton, Anita H.; Jordan, Robert; Lucas, Johna; Spana, Carl
Abstract: Background: Responder analyses are used to determine whether changes that occur during a clinical trial are clinically meaningful; for subjective endpoints such as those based on patient-reported outcomes (PROs), responder analyses are particularly useful. Aim: To identify the minimal clinically important difference (MCID) for selected scores on questionnaires assessing female sexual functioning and to use these differences to analyze the response in a large, controlled, phase 2b, dose-finding study of bremelanotide in premenopausal women with hypoactive sexual desire disorder (HSDD) and mixed HSDD/female sexual arousal disorder (FSAD). Methods: The responder analyses were performed for the change from baseline to end of study for a total of 7 endpoints. Each PRO endpoint was assessed using at least 1 of 4 types of responder analyses: a planned analysis anchored to MCIDs based on expert estimates (historical anchors); post hoc analyses based on self-reported global benefit; receiver operating characteristic (ROC) curves; and cumulative distribution function. The prespecified analysis groups were all female sexual dysfunction (FSD)-based diagnoses (all study participants), those with HSDD alone, and a combined group of those with FSAD alone plus those with mixed HSDD/FSAD. Post hoc analyses were also performed for subjects with mixed HSDD/FSAD with a primary diagnosis of HSDD. Outcomes: MCIDs based on the ROC curves for changes in Female Sexual Function Index–desire domain, Female Sexual Distress Scale–Desire/Arousal/Orgasm (FSDS-DAO) total score, FSDS-DAO item 13 and 14 scores, and number of satisfying sexual events. Results: Outcomes matched those based on input from clinical experts. For all 7 endpoints, responder rates at the 1.75 mg dose in the overall modified intention-to-treat population achieved statistical significance compared with placebo ( P ≤ .03). Clinical Implications: These responder definitions were subsequently used in the bremelanotide phase 3 registration studies (RECONNECT) that evaluated the safety and efficacy of the bremelanotide 1.75 mg subcutaneous dose in premenopausal women with HSDD. Strengths & Limitations: MCIDs for this study were based on changes from a single-blind phase to account for changes due to the placebo effect. These analyses were restricted to a study population composed only of premenopausal women with a clinical diagnosis of HSDD and/or FSAD and were based on data from the same clinical trial. Conclusion: Bremelanotide was safe and well tolerated and demonstrated significant improvement in efficacy vs placebo in the phase 2b trial. The multiple responder analyses offer a valuable approach for determining clinically important effects of bremelanotide for HSDD and FSAD.